No-touch endoscopic full-thickness resection technique for gastric gastrointestinal stromal tumors - Chen, Tao; Zhang, Yun-Wei; Lian, Jing-Jing; Zhang, Hai-Bin; Xu, Ai-Ping; Li, Fang; Yan, Xiao-Han; Duan, Ben-Song; Zhao, Zi-Ying; Chu, Yuan; Shen, Li; Cao, Jia; Zhang, Li; Zheng, Liang; Chu, Shu-Guang; Xu, Mei-Dong (Endoscopy, 2023)
Background There remain concerns regarding the technical feasibility of endoscopic resection for large gastrointestinal stromal tumors (GISTs), mainly relating to the risk of tumor rupture and the adequacy of the resection margins. This study aimed to evaluate the feasibility and therapeutic outcomes of the newly developed no-touch endoscopic full-thickness resection (NT-EFTR) technique for GISTs.Methods In this retrospective study, 92 patients with gastric GISTs undergoing NT-EFTR were included. Clinicopathological, endoscopic, and follow-up data were collected and analyzed.Results The median tumor size was 2.5 cm and en bloc resection was achieved in all patients with negative surgical margins. The median time of the NT-EFTR procedure was 59.5 minutes. Large tumors (> 3.0 cm), extraluminal tumor growth pattern, and large gastric defects were significant contributors to long operative times. Patients were discharged within 4 days postoperatively. During follow-up, all patients were free from local recurrence and distant metastasis.Conclusions NT-EFTR was a feasible method for the resection of gastric GISTs and can be expected to achieve complete radical resection. Large tumors with extraluminal growth and large gastric defects impact procedural difficulty.